Hemolivia species infecting Central American wood turtles (Rhinoclemmys pulcherrima manni) and problems with differential diagnosis within the genus Hemolivia - Živčicová Žaneta; Kvičerová Jana; Široký Pavel (Parasite, 2024)
Blood parasites of the genus Hemolivia Petit, Landau, Baccam and Lainson, 1990 (Adeleorina: Karyolysidae) are hemogregarines of ectothermic vertebrates, such as lizards, chelonians, and toads. Only five species of Hemolivia from vertebrate hosts and one from their tick vector have been described so far. In the present study, Central American wood turtles (Rhinoclemmys pulcherrima manni) originating from Southern Nicaragua were screened for the presence of hemogregarines. Ten out of 30 specimens (33.3%) were positive for Hemolivia using both approaches – microscopy and PCR-based analyses. Phylogenetic analyses based on the 18S rRNA gene revealed the presence of two haplotypes, both placed as sister taxa in the Hemolivia clade. Their phylogenetic position was supported by high bootstrap values and high posterior probabilities, suggesting that there are at least two new distinct haplotypes corresponding to two distinct species. However, the specimens of each haplotype were microscopically indistinguishable from each other based on the gamont morphology, therefore, only a single species could be described and named, as Hemolivia pulcherrima n. sp. We consider that the uniform morphology of the most common blood stages of species of the genus Hemolivia complicates their differential diagnosis. Sequence divergence and different host spectra, therefore, remain the only differentiating tools.